2017
DOI: 10.1177/1403494817731488
|View full text |Cite
|
Sign up to set email alerts
|

What patients think about choice in healthcare? A study on primary care services in Finland

Abstract: The Finnish primary care patients value choice, but they are critical of the availability of choice-relevant information. Choices of patients with complex health care needs should be supported by developing integrated care alternatives and by increasing the availability of information on existing care alternatives to meet their needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…These challenges regarding information and communication also have been reported in previous studies. For example, Aalto et al [ 46 ] have suggested that information on available services should be increased in conjunction with the development of integrated care alternatives. Additionally, the findings from a study conducted in the UK [ 18 ] stressed the importance of role clarity, particularly clients’ needs for sufficient information about the services that they are offered.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges regarding information and communication also have been reported in previous studies. For example, Aalto et al [ 46 ] have suggested that information on available services should be increased in conjunction with the development of integrated care alternatives. Additionally, the findings from a study conducted in the UK [ 18 ] stressed the importance of role clarity, particularly clients’ needs for sufficient information about the services that they are offered.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that influence consumer satisfaction can also be helpful to health-care provision by helping consumers make better choices (Owusu-Frimpong et al, 2010). Aalto et al (2018) show that consumers value choices if they are given the opportunity to make them, provided that the information is adequately given. Learnings…”
Section: Empirical Review and Hypotheses Developmentmentioning
confidence: 99%
“…The function of choice in improving healthcare quality is predicated on the hypothesis that healthcare providers will be encouraged to enhance their services, specifically when people ignore healthcare services because of their poor quality. As a result, the less educated and the elderly value the function of choice more because they have fewer options than those who are at a higher socioeconomic level (Aalto et al, 2017).…”
Section: Consumer Choices Towards Healthcare Servicesmentioning
confidence: 99%
“…Indeed, the quality of services is an essential component in choosing the right and proper healthcare. The function of choice in improving healthcare quality is predicated on the hypothesis that the healthcare providers will be encouraged to enhance their services, specifically when the people are ignoring the healthcare services because of their poor quality (Aalto et al, 2017).…”
Section: Factors That Affect the Choices Of The Consumers To Healthca...mentioning
confidence: 99%